Investigation on the efficency of methyl bromide gas on Spectrobates ceratoniae Zell. in store - M. S. Taheri; A. Farzaneh; B. Abazarian (نامه انجمن حشره‌شناسی ایران)
Spectrobates ceratonia Zell is known for the moment in Iran, as an agent facilitating the various micro-organism penetration inside the fruits.To prevent the introduction of larvae into the fruits and to keep them safe, we carried out some trials to evaluate Methyl-bromide at 35, 40 and 50 g/m3.The pretested fruits have had the following aspect: 27.08% without any larvae. 28.13% with larvae settled between sepales and the fruit-neck. Three months after fumigation, the results have been as following: 1- In control, all the fruits with larvae in any position inside them, were seriously injured.- 2-There have been no significant difference among the various dosage of Methyl bromide, but the fruits treated with 50 g/m3 had shown some necrosis on the skin.3- Mean percentages of injured fruits treated with 35 and 40 g/m3 had been 20.96% and 21.43% respectively, indicating that only the fruits with larvae among the seeds were eliminated. In all the experiments the temperature of the fumigation chamber has been maintained between 20 - 26 C and the fruits were exposed to gas two hours.